Clinical significance and influencing factors of carotid pulse wave velocity in patients with diabetic microangiopathy. Issue 3 (12th February 2022) - An, Xin; Li, Yihan; Shi, Shanshan; Ge, Lili; Li, Yuhong
Abstract: Purpose: To evaluate the utility of carotid ultrafast pulse wave velocity (PWV) and explore its influencing factors in patients with type 2 diabetes mellitus (T2DM) microangiopathy. Methods: Seventy‐seven patients with T2DM were divided into two groups according to the absence (Group A, n  = 45) or presence (Group B, n  = 32) of microangiopathy. The control group comprised 1544 healthy volunteers. Two‐dimensional ultrasonography was used to measure intima‐media thickness (IMT) of the carotid arteries, and ultrafast ultrasound imaging was used to measure PWV of the carotid arteries at the beginning of systole (PWV‐BS) and the end of systole (PWV‐ES). Results: The IMT, PWV‐BS, and PWV‐ES were higher in the T2DM group than in the control group, and the values in T2DM Group B were higher than those in Group A. IMT was positively correlated with PWV‐BS and PWV‐ES. Age and uric acid were influencing factors of PWV‐ES, while age, uric acid, body mass index, glycated hemoglobin, and urine albumin/creatinine ratio were influencing factors of PWV‐BS. PWV‐ES was a more sensitive predictor than PWV‐BS, and a PWV‐ES critical value predicted carotid elasticity in patients with T2DM microangiopathy. Conclusion: Ultrafast PWV can reflect early atherosclerosis and provide a noninvasive assessment of microangiopathy in patients with T2DM. Abstract : Pulse wave velocity (PWV) is shown for patients with type 2 diabetes without (1) and with (2) microangiopathy. PWV measurement was performed at the beginning of systole (BS) and at the end of systole (ES). The yellow boxes indicate areas of interest. The red line indicates automatic tracking of the front and rear walls. The abscissa represents time (s), and the vertical axis represents the anterior wall of the common carotid artery (mm). Red represents the movement of the anterior wall of the common carotid artery toward the probe. Blue represents the movement away from the probe. The brightness of the color indicates the speed of the movement. PWV‐BS corresponds to the slope of the bright red line, and PWV‐ES corresponds to the slope of the bright blue line. PWV was calculated as follows: PWV (m/s) = Δdistance (mm)/Δtime (ms).